0.7–1.8 GHz multiband digital polar transmitter using watt-class current-mode class-D CMOS power amplifier and digital envelope modulation technique for reduced spurious emissions. Issue 3 (23rd April 2013) - Nakatani, Toshifumi; Kimball, Donald F.; Larson, Lawrence E.; Asbeck, Peter M.
Abstract : A polar transmitter driven by digital input signals for envelope and phase is demonstrated, using a band-switching output resonator to achieve multiband operation. A new digital pulse width modulation algorithm is also shown to partially suppress spurious signals associated with the digital input envelope signal. The transmitter consists of a current-mode class-D (CMCD) CMOS power amplifier (PA), together with a buck converter with a dead-time generator for improved efficiency. The CMCD PA is tuned by band-switching capacitors that can handle up to 9 V, and is measured to have approximately 30 dBm output power with 31–35% drain efficiency under single-tone testing. The proposed spurious signal reduction technique works to partially suppress quantization noise without increasing power consumption. Overall efficiencies of 27.1/25.6% are obtained at 30.2/28.9 dBm continuous wave (CW) output powers and 0.85/1.75 GHz carrier frequencies, respectively. Spur suppression of 9–10 dB peak is achieved when the proposed algorithm is applied with wideband code division multiple access (WCDMA) modulation.